A review of the Mutillidae (Hymenoptera) of Azerbaijan - Lelej, Arkady S.; Proshchalykin, Maxim Yu.; Maharramov, Mahir M. (Zootaxa, 2022)
Fifty-eight species in 19 genera are recorded from Azerbaijan. A new synonymy is proposed for Mutilla sinuata Olivier, 1811 (=M. binotata Radoszkowski, 1879, syn. nov.; M. araratica Radoszkowski, 1890, syn. nov.) and Smicromyrme atrithorax (André, 1902) (=S. kurdus Skorikov, 1935, syn. nov.). The lectotypes of seven species: Agama caucasica Radoszkowski, 1885, ♂; Ephutomma radoszkovskii Skorikov, 1935, ♂; Mutilla armeniaca Kolenati, 1846, ♀; M. elongata Radoszkowski, 1885, ♂; M. binotata Radoszkowski 1879, ♀; M. araratica Radoszkowski 1890, ♀; and M. villosa Klug 1829, ♀ are designated. Fourteen species are recorded for the first time from Azerbaijan: Dasylabris (Inbaltilla) regalis (Fabricius, 1793); D. (I.) popovi Skorikov, 1935; D. (I.) shelkovnikovi Lelej, 1985; Dentilla erronea (André, 1900); Myrmilla (M.) calva (Villers, 1789); M. (Pseudomutilla) glabrata (Fabricius, 1775); M. (P.) vutshetitshi Skorikov, 1927; Physetopoda daghestanica (Radoszkowski, 1885); Pseudophotopsis armeniaca (Skorikov, 1935); Smicromyrme (Astomyrme) ausonius Invrea 1950; S. (Eremotilla) novaki Invrea, 1954; S. (Smicromyrme) ruficollis ruficollis (Fabricius, 1793); S. (S.) rufipes (Fabricius, 1787); and S. (S.) tristis Lelej, 1984. Four species are excluded from the list of Azerbaijan fauna. An updated key to three Palaearctic species of Macromyrme Lelej, 1984 is given and new combination and resurrected status are proposed for Macromyrme villosa (Klug, 1829). A cluster analysis of faunal similarities among Azerbaijan, Armenia, Georgia, Turkey and three regions of Russia (Crimea, North Caucasus, south of European part) for Mutillidae produce two major clusters (index similarity 0.4): Azerbaijan, Armenia, Turkey and Georgia (bootstrap probability 45 %), and three regions of Russia (bootstrap probability 87 %). This demonstrates the important boundary between two large biogeographical subregions of Palaearctic: Mediterranean and Euro-Siberian. The Azerbaijan fauna, especially Nakhchivan Autonomous Republic, is most closely related with the Armenian fauna.